2018
DOI: 10.1149/08605.0077ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Proximity Gettering Design of Hydrocarbon Molecular Ion Implanted Silicon Wafers Using Direct Bonding Technique for Advanced CMOS Image Sensors: A Review

Abstract: We developed high gettering capability silicon wafers for advanced CMOS image sensors using hydrocarbon molecular ion implantation and surface activated direct wafer bonding (SAB). We found that this novel wafer has three unique characteristics for the improvement of CMOS image sensor device performance. The first is metallic impurity gettering capability in the hydrocarbon ion implantation projection range during CMOS device fabrication. The second is the oxygen out-diffusion barrier effect; this wafer can co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Second, our previous study demonstrated that pn-junction leakage current of pn-junction diode dramatically decreased by combination of both hydrocarbon–molecular implantation and surface activated wafer bonding (SAB) techniques compared to without SAB [65,66]. The pn-junction leakage current determined some factors such as metallic impurity contamination in space-charge region and interface state defect in device isolation region.…”
Section: Gettering Technology Design For Back-side-illuminated Cmomentioning
confidence: 99%
See 2 more Smart Citations
“…Second, our previous study demonstrated that pn-junction leakage current of pn-junction diode dramatically decreased by combination of both hydrocarbon–molecular implantation and surface activated wafer bonding (SAB) techniques compared to without SAB [65,66]. The pn-junction leakage current determined some factors such as metallic impurity contamination in space-charge region and interface state defect in device isolation region.…”
Section: Gettering Technology Design For Back-side-illuminated Cmomentioning
confidence: 99%
“…Third, we demonstrated that the hydrogen out-diffused to silicon epitaxial layer (device active region) from hydrogen storage in hydrocarbon–molecular–ion projection range during the heat treatment [35,65,66]. This hydrogen of out diffusion amount is 10 12 to 10 13 cm −2 measured by SIMS after heat treatment [70].…”
Section: Gettering Technology Design For Back-side-illuminated Cmomentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Such a method is expected to be an effective way to reduce D it 16,17 in advanced CIS, because hydrogen that diffused out from the Si bulk can be provided to the device active region without being trapped by multiple dielectric layers in advanced CIS. 18,19 On the basis of this concept, our group has been developing a hydrocarbon-molecularion-implanted epitaxial Si wafer 17,20 for CIS. The fabrication process for hydrocarbon-molecular-ion-implanted epitaxial Si wafer is very simple, that is, implantation of hydrocarbon molecular (C 3 H 5 or C 3 H 6 ) ions into a Si substrate followed by homoepitaxial growth on the substrate.…”
mentioning
confidence: 99%